Vibration sensor for monitoring systems of construction elements of high-voltage power lines - I. V. Bryakin; I. V. Bochkarev (Известия высших учебных заведений: Проблемы энергетики)
PURPOSE. To develop a differential parametric inductive transducer of vibration values into an electrical signal, which is a vibration displacement sensor (DV) with a new principle of operation. Theoretically substantiate the performance of the proposed DV. To develop a new system for vibroacoustic monitoring of the technical condition of overhead power transmission line (TL) supports using the proposed DV. METHODS. When solving this goal, the theory of parametric transducers and the main provisions of the theory of vibration diagnostics were used. RESULTS. The design feature of the developed DV is the absence of an excitation coil, and its functional elements form a full-fledged measuring bridge, the arms of which include interturn capacitances of the windings of the first and second measuring coils, as well as capacitances formed by a metal cylindrical electrode with a coaxially located inside it ferromagnetic rod and the first lower rows of wire windings of the measuring coils. The bridge circuit operates in a resonant mode, which ensures the high sensitivity of the proposed sensor, and the quadrature conversion of the information signal provides the necessary level of noise immunity. The received signal is a functional dependence of the output voltage of the measuring bridge on the magnitude of external vibrations, the characteristics of the temporary realizations of which reflect the degradation processes occurring in the power transmission line supports. CONCLUSION. The proposed system for monitoring the integrity of power transmission line supports is actually a distributed real-time sensor network that implements PLC technology. The DV of each sensor module registers microvibrations of the structural elements of the corresponding power transmission line support, caused by natural disturbing factors during their operation, and converts them into an electrical information signal, which forms the basis of monitoring information about the current state of the power transmission line support structural elements.